High-frequency germ-line transmission of plasmid DNA sequences injected into fertilized zebrafish eggs. - Culp, P (1991)
With the goal of developing techniques for DNA insertional mutagenesis in zebrafish, we established procedures for rapidly obtaining and injecting large numbers of fertilized eggs. Using either of two plasmid constructs, we injected uncut DNA into fertilized eggs at the one- or two-cell stage. Fish hatched from injected eggs were raised to sexual maturity, and the frequency of transgenic founder fish was determined by pair-mating the fish and testing DNA extracted from pools of their 16-hr-old offspring by the polymerase chain reaction (PCR) and then Southern analysis. Eggs injected with one of two different plasmids yielded no transgenic fish, but 7-25% (19 of 115 overall) of the eggs injected with the other plasmid transmitted the injected sequences to their offspring (F1). Of seven lines studied further, all were able to pass the foreign DNA sequences to the next (F2) generation. Inheritance in the F2 generation was Mendelian in the five lines tested. PCR and Southern analysis indicated that the plasmid sequences were present in multiple copies, probably tandemly arranged. Two founder fish carried more than one independent integration of the plasmid sequences. The line studied in more detail was a mosaic carrying two independently segregating copies of the transgene in one germ cell and a third copy in another germ-line precursor cell. The ability to obtain and inject large numbers of zebrafish eggs combined with a high frequency of germ-line integration may be steps toward the goal of being able to perform insertional mutagenesis with this organism.